Implementation of Deep Learning in The Kurikulum Merdeka using AI as An Innovative Learning Companion for The Yos Tech Community - Susilowati, Meme; Nurwegiono, Muhammad; Wilujeng, Lilis Lestari (LPPM Universitas Ma Chung, 2025)
The rapid growth of information and communication technology has reshaped educational practices and supported the implementation of Indonesia’s Independent Curriculum (Kurikulum Merdeka), which emphasizes a deep learning approach. However, many schools still struggle to integrate technology and Artificial Intelligence (AI) meaningfully into classroom practice. This community service program was conducted at SDK Yos Sudarso Kepanjen to strengthen teachers’ and students’ technological literacy and to apply deep learning principles using AI-based tools. The program adopted the Information System Project Management framework, comprising five stages: initiating, planning, execution, monitoring and controlling, and closing. Activities included a needs analysis, the development of training modules, online Training of Trainers (TOT) for student facilitators, four onsite training sessions for teachers and students, a digital product showcase, and ongoing evaluation. The program involved 22 students (grades IV–V) and six teachers over an eight-month period. Pre- and post-training questionnaires indicated a 35% increase in digital skills and a 42% rise in student learning motivation. Teachers became more confident in utilizing tools such as Canva and ChatGPT, while students showed greater engagement and creativity in technology-supported learning tasks. The revitalized YosTech club emerged as a school-based digital learning community that fosters 21st-century skills. The findings suggest that structured AI-supported training can effectively bridge the gap between policy expectations of deep learning and actual practice at the elementary school level.